2002
DOI: 10.1128/aac.46.5.1340-1344.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Specific Antibodies against Streptococcus pneumoniae on Pharmacodynamic Parameters of β-Lactams in a Mouse Sepsis Model

Abstract: A dose-ranging study to investigate the in vivo effects of the presence of specific antibodies on the efficacy of ␤-lactam treatment of sepsis caused by Streptococcus pneumoniae (non-␤-lactam-susceptible serotype 6B isolate) was performed with a BALB/c mouse model. Hyperimmune serum was obtained from mice immunized with the heat-inactivated strain. The rate of mortality was 100% in nontreated animals in the absence of specific antibodies. A single injection of a one-half or one-quarter dilution of hyperimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 15 publications
(15 reference statements)
1
31
0
Order By: Relevance
“…Once the MLD had been determined, 2ϫ MLD was used as the infective inoculum (challenge dose). The procedure for this experiment was carried out as described previously, with modifications (3,20).…”
Section: Methodsmentioning
confidence: 99%
“…Once the MLD had been determined, 2ϫ MLD was used as the infective inoculum (challenge dose). The procedure for this experiment was carried out as described previously, with modifications (3,20).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies (2,21,22), a synergistic effect between the 3.12-mg/kg subtherapeutic dose and the 1/4 dilution of hyperimmune serum specific to the infecting strain, a 6B non-amoxicillin-resistant (amoxicillin MIC of 4 g/ml) S. pneumoniae strain (different from the serotype 6B strain used in the present study), with respect to mortality, was not clearly demonstrated due to the high protection provided by immunization. With respect to synergism, the more interesting interactions are those that result in enhanced rates or absolute magnitudes of bacterial killing by the combination compared with those by either drug alone (8), and it has been proposed that this effect be measured in vivo (17).…”
Section: Discussionmentioning
confidence: 99%
“…Amoxicillin concentrations in serum in six healthy animals after a single subcutaneous dose of antibiotic were determined as previously described (2) to confirm the concentrations determined in previous experiments (2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations